Educational orientation and employer influenced pedagogy: Practice and policy insights from three programmes in Europe. Issue 4 (9th November 2015) - Devins, David; Ferrandez-Berrueco, Reina; Kekale, Tauno
Abstract : Purpose: – The purpose of this paper is to explore the relationship between educational orientation and employer influenced pedagogy and to consider some implications for work-based learning (WBL) higher education (HE) policy and practice in Europe. Design/methodology/approach: – The paper draws on purposefully selected case studies to describe the key attributes of WBL related pedagogy associated with three HE programmes in Finland, Spain and the UK. Findings: – The national regulatory environment has a key role to play in issues associated with WBL pedagogy. The case studies also demonstrate a pluralistic approach to pedagogy and the key role that employers play in both providing regular intelligence to inform curriculum design and contributing to pedagogy. Research limitations/implications: – The small number of case studies limits the opportunity for generalisation and the level of analysis masks subtle and interesting differentiations in pedagogy worthy of further exploration. Practical implications: – The paper highlights implications for government to provide the vision and regulatory environment to encourage WBL and for universities and academics to design and implement innovative, pluralist pedagogies. Originality/value: – The paper provides a new framework and a unique analysis of programme level case studies from three European countries.